An explorative study of social media content marketing influence on purchase intention of cake - Purnomo, Anselmus Hansel Tanthio; Nasution, Reza Ashari (Journal of Business and Management, 2020)
Abstract. The Indonesian cake market is already crowded which means numbers of competitor for businesses and tons of choices for customers. It can be difficult for cake business in an already crowded market to stand out and in the same time it can be confusing for customers - which eventually end up going to the same cake store to save time. Even if social media such as Instagram helps both sides to exchange information faster, there will still be a lot of cake businesses on Instagram which can overwhelm the customers. Combined with Instagram, content marketing can be the answer to both build relationship with customer and increase purchase intention. The question is: when purchasing a cake, what information do customers need and what information do brands need to share? This study aims to discover types of contents in content marketing on Instagram that cake brand needs to be shared and why, based on the customer itself. Through the analysis using initial and focused coding, the researcher found there are 13 types of content that increase purchase intention, which are: Brand's social responsibility, People's opinion of the product, Brand's credibility, Information to help purchase, Product's validation, Product's visual display, What is in the product, Product's experience, Product's production process, Discount-related notification, Story Behind it, Product’s Information, Interactive activity with the brand. As for the reason why, the researcher discovered the following reasons: Make purchase process easier, Chance of getting better deals financially, Understand the reason for the price, Feeling better of using money, Actual product experience, Know how to get good experience, Social Trend, Increase brand's trustability, Validations of the product, Create a curiosity that needs to be answered, Visually Satisfying, Clear expectation of the result, and Share valuable knowledge. This research finds that to increase one’s purchase intention, brands should start by giving various type of content that explains the product and followed by content that is not directly about the product, rather about what’s around the product (method of purchase, discount, the brand itself, etc.). The need for validation of the information also can be seen.Keywords: cake market, content marketing, Instagram, purchase intention, types of content.